Spelling First : Word-Level Activites in Context the Curriculum 2 - Barke, Ray; Moorcroft, Christine (Cheltenham : Nelson Thornes, 2002)
This supplementary series of textbooks and teacher files has been developed to encourage confident writers in secondary schools, meeting the need of effective literacy that has been identified as the key to raising standards across all curriculum areas.
Keywords: Anglais (Langue) -- Orthographe Ouvrages pour la jeunesse; Anglais (Langue) -- Orthographe Problèmes et exercices; Juvenile literature Juvenile works Problems and exercises